Developing local food with taro cultivation in Tempursari Village, Candimulyo, Magelang - Retno Rusdjijati; Alfian Syarifuddin; Oesman Raliby Al Manan; Agus Suprapto (Universitas Muhammadiyah Magelang, 2022)
Local food is created and developed in accordance with the potential, resources, and local culture of the area. As a result, the type, quantity, and quality of local food products will vary depending on the regional conditions. Tempursari Village has a fairly high diversity of food where 8 types of taro grow there. The taro cultivation activity was attended by 20 members of the Mekar Sari Farmers Association. The implementation stages include village potential surveys, discussions with farmer groups, cultivation training, plant maintenance, monitoring and evaluation. The results of these activities are able to increase land productivity so as to provide an alternative in improving the economy of farmer groups as a way of diversifying food by optimally utilizing land resources which provides a positive value for farmer income.